The Use of Season Ticket Incentives in Major League Baseball - Kaitlin Poe; John Drea (Journal of Applied Sports Management, 2020)
A study of Major League Baseball season ticket promotional incentives found that the most popular types of incentives provided to season seat holders (SSHs) were exclusive offers, complementary items, discounts, ticket options and services, and payment plans. Offering a payment plan to SSHs was positively associated with higher average game attendance. Payment plans were more commonly associated with teams with higher winning percentages over the past three seasons and with teams that filled a higher percentage of their stadium capacity. Teams that fill more of their stadium capacity were also found to offer fewer categories of season ticket incentives to SSHs.
Keywords: Consumer behavior; Management; MLB; Promotions; Season tickets